Feed and forage development in mixed crop–livestock systems of the Ethiopian highlands: Africa RISING project research experience - Mekonnen, Kindu; Bezabih, Melkamu; Thorne, Peter J.; Gebreyes, Million; Hammond, James; Adie, Aberra (Wiley, 2022)
Africa Research in Sustainable Intensification for Next Generation (RISING) project has conducted action research on livestock feed and forages starting in 2012 to bridge gaps on feed availability and quality. The objectives of this paper are to share approaches on how Africa RISING project enabled smallholder farmers to intensify feed and forage resources; present research findings of selected cultivated forages, fodder trees, and postharvest feed and forage utilization innovations; and highlight key lessons evolving from the feed and forage action research and scaling interventions. The project established partnership with CGIAR and local partners, conducted participatory need assessment, prioritized researchable issues, identified and validated different forages and utilization innovations, and created development partnership to facilitate wider scaling. Training activities and multistakeholder platforms were used to enhance cross learning of project partners. The cultivated forages grown under farmers’ fields and management conditions provided high biomass yield of good nutritional quality. For instance, oat (Avena sativa L.)–vetch (Vicia villosa Roth) mixture, lablab [Lablab purpureus (L.) Sweet], vetch–desho grass (Pennisetum pedicellatum Trin.) intercropping, sweet lupin (Lupinus albus L.), alfalfa (Medicago sativa L.), and fodder beet (Beta vulgaris L.) yielded on average 15, 3.4, 5.5, 2.9, 15.3, and 20.2 t dry matter ha−1, respectively. Animal response trials showed an increase in milk yield of 30–50% with supplementation of oat–vetch mixture and fodder beet. Feed wastage was considerably reduced (>30%) due to the use of feed troughs and storage sheds, with high economic incentives to invest in such innovations. Integrating and intensifying feed and forage resources and postharvest innovations at farm level remains a priority to improve livestock productivity and food security.